Early Parenting Stress Links Obstetric Complications and Child Psychopathology in Middle Childhood in an At-Risk Sample. Issue 1 (January 2022) - Fuchs, Anna; Resch, Franz; Kaess, Michael; Moehler, Eva
ABSTRACT: Objective: Obstetric complications (OCs) are adverse events during pregnancy, birth, or immediately after birth. Evidence on cumulative OC and longitudinal associations with child psychopathology is sparse. Prospective studies testing mediating pathways such as parenting stress are needed. This study aimed to investigate the impact of OC on child psychopathology in middle childhood and to highlight whether and which type of parenting stress specifically mediates this association. Methods: We investigated n = 54 mother-child dyads from 5 months to 8 years of age. Child psychopathology at 8 years and parenting stress at 12 months were assessed using the Child Behavior Checklist (CBCL) and the Parenting Stress Index. OCs were evaluated by the Steinhausen Questionnaire and through access to official pregnancy records at the 5-month visit. Half of the mothers had experienced early-life maltreatment (ELM), assessed with the Childhood Trauma Questionnaire. Results: There was a significant indirect effect of maternal parenting stress at 12 months mediating the association between OC and child psychopathology at 8 years ( β = 0.26; p < 0.01; 95% [0.35–1.83]). A significant proportion of 35% of CBCL-variance was explained. The significant effect remained even when maternal ELM and maternal psychological distress were controlled for. On the subscale level, only the "Difficult Child" subscale was a significant mediator. Conclusion: Our findings suggest that parenting stress should be targeted to prevent adverse effects of OC on child psychopathology. More research focusing on families subjected to OC is needed to highlight how maternal parenting stress and child regulatory functioning interact to affect child development longitudinally.